2014
DOI: 10.4274/tjh.2012.0154
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Iron Study in Myelodysplasia

Abstract: Objective: Hepcidin plays a pivotal role in iron homeostasis. It is predominantly produced by hepatocytes and inhibits iron release from macrophages and iron uptake by intestinal epithelial cells. Competitive ELISA is the current method of choice for the quantification of serum hepcidin because of its lower detection limit, low costs, and high throughput. This study aims to discuss the role of hepcidin in the pathogenesis of iron overload in recently diagnosed myelodysplasia (MDS) cases. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…The remaining 53 citations were subjected to a thorough full-text investigation. Ultimately, 12 references were included in this systematic review [20][21][22][23][24][25][26][27][28][29][30][31]. The primary reason for excluding full-text citations was a lack of complete data on hepcidin levels in patients with MDS.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 53 citations were subjected to a thorough full-text investigation. Ultimately, 12 references were included in this systematic review [20][21][22][23][24][25][26][27][28][29][30][31]. The primary reason for excluding full-text citations was a lack of complete data on hepcidin levels in patients with MDS.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Our specific search terms were: "hepcidin" and "myelodysplastic syndromes" with no limitations on language or publication type. We also conducted manual searches of the bibliographies of all included studies [20][21][22][23][24][25][26][27][28][29][30][31] and reviewed articles to identify any remaining studies. We utilized Zotero version 6.0.4 (Corporation for Digital Scholarship, Vienna, VA, USA) to extract duplicate research.…”
Section: Search Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Iron can inhibit osteoblast formation [115] and would be expected to affect macrophage phagocytosis activity. Hepcidin levels are quite variable in MDS [116,117] and there is evidence that iron chelation can lead to hematologic improvement in some patients [118].…”
Section: Cellular Inflammatory Mediators In Mdsmentioning
confidence: 99%
“…In intestinal epithelial cells, it is believed to downregulate divalent metal transporter 1, which is involved in the transfer of iron across the intestinal wall. 3 It has been reported that ineffective erythropoiesis enhances iron absorption in MDS through downregulation of hepcidin and its prohormones such that SF rises. 4 Plants of the ginger family have been credited with hepatoprotective activity.…”
Section: Introductionmentioning
confidence: 99%